PENGARUH KEBIJAKAN HUTANG DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ45 - Asep Saeful Falah; Euis Deliar Noor Badriyah; Fitriani; Fitriani Fitriani (Journal of Innovation Research and Knowledge, 2026)
This research aims to determine the influence of debt policy and dividend policy on firm value for companies listed in the LQ45 index on the Indonesia Stock Exchange during the period 2021–2023. This research uses a quantitative method with panel data regression. Data processing was performed using EViews 12 software. The sample was determined using purposive sampling and consisted of 13 companies with complete data on the Debt to Equity Ratio (DER), dividend payout ratio (DPR), and price-to-book value (PBV) variables. With an observation period of three years, a total of 39 observation data points were analyzed. The research results indicate that debt policy has a positive and significant partial effect on firm value, dividend policy has a negative and significant effect on firm value. And simultaneously, debt policy and dividend policy have a significant effect on firm value.